The Effect of Yuan Exchange Rate to Islamic Banking Credit Risk in Asia Case Study of Indonesia - Wahyu Khoirun Nisa; Patria Yunita; Ayis Mukholik (Sekolah Tinggi Ekonomi dan Perbankan Islam Mr. Sjafruddin Prawiranegara, 2023)
This study aims to analyze the effect of the yuan exchange rate on non- performing financing in Islamic banking for the period March 2012 to February 2022. The type of data used in this study is quantitative data and the source of data used in this study is secondary data obtained from the official website of the Authority. Financial Services (OJK) and Bank Indonesia (BI) . The data analysis model in this study uses multinomial logit regression analysis, where multinomial logistic regression is a logistic regression used when the dependent variable has a polychotomous or multinomial scale. The results of the analysis show that the yuan exchangeAuthor I ArticleTitle rate has a positive and insignificant effect on non-performing financing of Islamic banking when the NPF ratio is in a Medium Risk condition. In High Risk the yuan exchange rate has a positive and significant effect on non- performing financing of Islamic banking and when in Very High Risk conditions, the yuan exchange rate has a positive and insignificant effect on non-performing financing of Islamic banking. The Pseudo R-Square value is 0.1057 which means that the value of the variation of the dependent variable that can be explained by the independent variable is 10.57% while the remaining 89.43% is explained by other variables.